2014
DOI: 10.1007/s11235-014-9942-z
|View full text |Cite
|
Sign up to set email alerts
|

Toward open service access to policy and charging control in evolved packet system

Abstract: The emerging multimedia communications are expected to enable simultaneous services with high throughput and low-latency requirements. Ensuring appropriate quality of service (QoS) for multimedia services is one of the challenges that network operators have to cope with in the Evolved Packet System (EPS). The mechanism which allows policy based authorization and usage control of QoS resources intended for multimedia traffic in EPS is called Policy and Charging Control (PCC). The paper investigates the capabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The architectural concept of the trusted 3P-based management system assumes a hierarchical organization of 3P agents at the international, national and regional levels. In [14], the open the traffic is crossing more than two domains, there is a risk that the E2E QoS requirements may not be achieved.…”
Section: Related Workmentioning
confidence: 99%
“…The architectural concept of the trusted 3P-based management system assumes a hierarchical organization of 3P agents at the international, national and regional levels. In [14], the open the traffic is crossing more than two domains, there is a risk that the E2E QoS requirements may not be achieved.…”
Section: Related Workmentioning
confidence: 99%
“…Further, the open access to intersystem handover control enables creation and deployment of innovative applications. The benefits of open access to network functionality in the core network are studied in [24].…”
Section: Related Work and Research Motivationmentioning
confidence: 99%
“…The operations, administration, and management (OAM) in packet-based networks represents a generic technological framework that covers an area of awareness of the state of network resources, available capacity of individual network segments, connectivity verification, fault detection, and network management [5]. It is based on collecting information on the state of resources of different network domains and represents the enabler for the dynamic control of network resources through standard mechanisms defined for Next-Generation Network Architecture [6], 3GPP [7], and IETF [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the standardization level, there is no unified understanding of required features and mechanisms that must be supported [5]. Following a review of related work in the field of standardization, specifications, and recommendations of the International Telecommunication Union (ITU-T) [8], Internet Engineering Task Force (IETF) [9, 10], Metro Ethernet Forum (MEF) [11], Institute of Electrical and Electronics Engineers (IEEE) [12], and other scientific sources [7, 13], it can be concluded that no such framework exists that would define the concept of OAM in the transport and application layers of a TCP/IP protocol stack. The existing methods and concepts are limited to physical, data-link, and network layers.…”
Section: Introductionmentioning
confidence: 99%